Profil Habits of Mind Siswa SMA dalam Pemecahan Masalah Matematika - Putri, Tessa Felyani; Sugiatno, Sugiatno; Bistari, Bistari (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This study aims to describe the habits of mind possessed by high, medium, and low class XI high school students in solving mathematical problems on linear program material studied from persisting, thinking flexibly, applying past knowledge to new situations, and metacognition. Habits of mind that are the focus of this study consist of four indicators, namely persisting, thinking flexibly, applying past knowledge to new situations, and metacognition. The research subjects were students of class XI MIPA 4 SMAS Mujahidin Pontianak and the object of research was habits of mind in mathematics problem solving. Explanatory sequential mixed method design is the method of this research with its instruments, namely math problem solving test questions, habits of mind questionnaire, and interview guidelines. The results of the discussion show that the habits of mind possessed by high category students in solving mathematics are persisting, thinking flexibly, applying past knowledge to new situations, and metacognition. Habits of mind owned by medium category students are persisting, thinking flexibly, and applying past knowledge to new situations. Habits of mind possessed by low category students are persisting.